2023
DOI: 10.3390/molecules28052372
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Marker Compounds and In Vitro Toxicity Evaluation of Two Portuguese Asphodelus Leaf Extracts

Abstract: The leaves of Asphodelus bento-rainhae subsp. bento-rainhae, an endemic Portuguese species, and Asphodelus macrocarpus subsp. macrocarpus have been used as food, and traditionally as medicine, for treating ulcers, urinary tract, and inflammatory disorders. The present study aims to establish the phytochemical profile of the main secondary metabolites, together with the antimicrobial, antioxidant and toxicity assessments of both Asphodelus leaf 70% ethanol extracts. Phytochemical screenings were conducted by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…CgAE: Campylanthus glaber aqueous extract; CgEE: Campylanthus glaber ethanolic extract; PC (positive control); SD (standard deviation); (1)-2-nitrofluorene; (2)-sodium azide; (3)-tert-butyl hydroperoxide; (4)-9-aminoacridine. * These values are similar to those obtained byMalmir et al (2023) [31] and Malu et al (2022)[32], since this study was performed simultaneously.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…CgAE: Campylanthus glaber aqueous extract; CgEE: Campylanthus glaber ethanolic extract; PC (positive control); SD (standard deviation); (1)-2-nitrofluorene; (2)-sodium azide; (3)-tert-butyl hydroperoxide; (4)-9-aminoacridine. * These values are similar to those obtained byMalmir et al (2023) [31] and Malu et al (2022)[32], since this study was performed simultaneously.…”
supporting
confidence: 92%
“…No. HB-8065, Middlesex, UK), according to [31]. Briefly, 48 h after inoculation, the HepG2 culture medium was replaced by fresh medium with CgAE and CgEE (9:1) at final concentrations ranging from 50 to 1000 µg/mL.…”
Section: In Vitro Assessment Of Cytotoxicitymentioning
confidence: 99%
“…A recent study characterized the substances in the dried root tubers and showed that terpenoids were the main class of secondary metabolites in the extracts [ 24 ]. The leaves of AbR were used as food and in traditional medicine to treat ulcers and urinary and inflammatory disorders [ 25 ], and also as fertilizer and fodder in Portugal [ 26 ]. The ethyl ether fractions demonstrated the highest antibacterial activity against all Gram-positive microorganisms, with aloe-emodin as one of the main marker compounds that are highly active against Staphylococcus epidermidis , and the ethyl acetate fractions exhibited the highest antioxidant activity [ 25 ].…”
Section: Introductionmentioning
confidence: 99%